Selfhood and alterity: schizophrenic experience between Blankenburg and Tatossian - Guardascione, Alessandro (Frontiers in Psychology, 2023)
This paper presents a critical comparison between two phenomenological accounts of schizophrenic experience: on the one side, Blankenburg’s seminal work on the basal disturbance (Grundstörung) of schizophrenia as loss of natural self-evidence (Natürlichen Selbstverständlichkeit); on the other side, Tatossian’s insight, briefly elaborated in a lecture presented in Heidelberg in 1994 and largely forgotten by the relevant literature. Whereas the former mainly develops an intersubjective reading of schizophrenia, the latter suggests an intrasubjective understanding. Indeed, for Blankenburg, schizophrenic experience can be broadly characterized as a progressive impoverishment of our rootedness in the social world, leading to derealization and depersonalization. In this respect, Tatossian takes schizophrenic autism not as the effect of a loss of originary sociality but as the result of a deeper disproportion. For Tatossian, schizophrenia is characterized, ultimately, by a basic self-disorder or alteration that consists in the breakdown of the twofold dimension of transcendental subjectivity, encompassing both constituting consciousness and phenomenologizing onlooker. In this sense, his interpretation of schizophrenic disorders is closer to the ipseity-disturbance model. I show that while Blankenburg and Tatossian share a dialectical understanding of schizophrenia by pointing to basic modifications of the “transcendental organization” of experience, their divergence originates from a different reading of the phenomenological epoché. Except for the clinical perspective, the point of contention between Blankenburg and Tatossian seems to concern their use of internal resources of the Husserlian phenomenology. By presenting the philosophical presuppositions of their analyses, I discuss two key figures of phenomenological psychopathology by showing how their debate on the meaning of schizophrenic experience can be reframed by looking at the relationship between transcendental subjectivity and intersubjectivity in Husserl’s phenomenology.